ANALISIS TEKS PUISI DALAM BUKU PEGANGAN GURU BUKU PENILAIAN AUTENTIK PENERBIT ERLANGGA DI KELAS V SEKOLAH DASAR - Indra P.S, M. Zuhri Indra P.S M. Zuhri; Kurniaman, Otang Kurniaman Otang; Noviana, Eddy Noviana Eddy (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This study, entitled Analysis of the poem text in teacher handbooks, book publishers authentic assessment v erlangga in primary school classroom. In the 2013 curriculum learning poetry still be learned in elementary school therefore collection of poems in which there are some poems which will be analyzed in order to understand the meaning of the poem. The method used in this research is descriptive method through literature. Descriptive research method can be interpreted as a troubleshooting procedure investigated by describing or depicting the state of the subject or object at the present time based on facts that appear or as it is. Poems contained in the book authentic assessment fifth grade elementary school publisher grants the use of figurative language, there are 6 kinds of figurative language that is personification, sinekdot, allegorical, parable epics, metonymy, metaphor and hipalase while in some poetry still use the meaning of denotation as in poetry entitled Lingkunganku and Negeriku.Keywords: Bupena, Poetry, Analysis.